Kontribusi Parental Mediation terhadap Kecenderungan Problematic Internet Use pada Remaja di SMP SFX - Paramitha Paramitha; Margaretha Purwanti (Provitae: Jurnal Psikologi Pendidikan, 2020)
Continuous and uncontrolled internet usage in adolescents can lead to dependency on the internet or problematic internet use (PIU). To minimize this, parental mediation is needed to encourage teenagers to use internet wisely. This study aimed to determine the five types of parental mediation (restrictive mediation, active mediation of internet safety, active mediation of internet use, technical mediation, monitoring) contribution together towards the tendency of PIU in adolescents. This is a correlational-quantitative research using parental mediation and PIU scale. The participants were 214 adolescents of class VII-IX at SFX Junior High School who were selected by purposive sampling method. Around 71.97% of adolescents have a tendency to PIU classified as average-problem group. They use the internet to finding entertainment, opening social media, and chatting for 4-6 hours per day. The use of mediation strategies by parents in adolescents still varies, most adolescents perceive parents using technical mediation (around 25.23%) in assisting adolescents’ internet use. Through multiple regression analysis, the five types of parental mediation together do not have a significant contribution in predicting PIU. The greater contribution comes from variables outside the five types of parental mediation (around 95.2%), such as gender, purpose and time of internet use, socioeconomic condition, psychological condition, peers, and class environment. Based on the results of this study, it appears that parents still do not have deep knowledge about mediation strategies in addressing adolescents’ internet use. The recommendation is to provide training for parents to improve their knowledge and skills in assisting adolescents’ internet use.